2016
DOI: 10.1016/j.fct.2016.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity assessment of the flavouring agent, perillaldehyde

Abstract: Perillaldehyde, a natural monocyclic terpenoid found most abundantly in the herb perilla, has a long history of use as a flavouring ingredient to add spiciness and citrus taste to foods. Previously, it was judged to be safe by several international expert panels. To confirm the safety of flavourings placed on the European Union list of flavourings, perillaldehyde was selected by the European Food Safety Authority as a representative of a subgroup of alicyclic aldehyde flavouring substances to be evaluated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 13 publications
2
52
0
Order By: Relevance
“…Perillaldehyde (PAE), a secondary metabolite in perilla plants, has been used extensively as a flavouring ingredient to add spice and citrus tastes to foods (Wang et al, 2008). Moreover, since 1948, PAE has been designated as unlikely to harm human health by the Japanese Ministry of Health, Labour and Welfare under the Food Sanitation Act (Hobbs et al, 2016). PAE exhibits antioxidant, antidepressant and other biological properties (Ito et al, 2011;Jin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Perillaldehyde (PAE), a secondary metabolite in perilla plants, has been used extensively as a flavouring ingredient to add spice and citrus tastes to foods (Wang et al, 2008). Moreover, since 1948, PAE has been designated as unlikely to harm human health by the Japanese Ministry of Health, Labour and Welfare under the Food Sanitation Act (Hobbs et al, 2016). PAE exhibits antioxidant, antidepressant and other biological properties (Ito et al, 2011;Jin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The Panel noted that on the basis of OECD TG 489, the evaluation should be based on a comparison between treatment-induced values and the concurrent vehicle control, the consideration of a potential dose-response relationship and on a comparison of treatment-induced values with (appropriate) historical negative control data, not primarily on a comparison between vehicle/positive control experimental data and historical controls. Hobbs et al (2016) report three different ranges of historical control, two of the reported ranges are new and not overlapping. However, the range of historical negative control is still wide and no justification on the overlapping range is provided.…”
Section: The Two Articles Indicatementioning
confidence: 96%
“…‘The international effort to validate the in vivo comet assay for the detection of genotoxic carcinogens, coordinated by the Japanese Center for the Validation of Alternative Methods (JaCVAM), concluded that histopathology remains the “gold standard” for assessing tissue cytotoxicity, and changes in % tail DNA require careful interpretation when measured in conjunction with severe histopathological changes (Uno et al., ). (..) The perillaldehyde comet findings (both the group mean and individual animal data) are well within this upper limit for acceptable vehicle control values further supporting the conclusion that the small increase in tail intensity observed in the liver following administration at 700 mg/kg per day was not biologically relevant and was most likely an artefact of the observed hepatic cytotoxicity’ (Hobbs et al., ).…”
mentioning
confidence: 96%
See 2 more Smart Citations